Quantitative Measurement of Cerebrovascular Reactivity by Blood Oxygen Level-Dependent MR Imaging in Patients with Intracranial Stenosis: Preoperative Cerebrovascular Reactivity Predicts the Effect of Extracranial-Intracranial Bypass Surgery - Mandell, D.M.; Han, J.S.; Poublanc, J.; Crawley, A.P.; Fierstra, J.; Tymianski, M.; Fisher, J.A.; Mikulis, D.J. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: CVR is a measure of cerebral hemodynamic impairment. A recently validated technique quantifies CVR by using a precise CO2 vasodilatory stimulus and BOLD MR imaging. Our aim was to determine whether preoperative CO2 BOLD CVR predicts the hemodynamic effect of ECIC bypass surgery in patients with intracranial steno-occlusive disease. MATERIALS AND METHODS: Twenty-five patients undergoing ECIC bypass surgery for treatment of intracranial stenosis or occlusion were recruited. CVR was measured preoperatively and postoperatively and expressed as %ΔBOLD MR signal intensity per mm Hg ΔPetCO2. Using normative data from healthy subjects, we stratified patients on the basis of preoperative CVR into 3 groups: normal CVR, reduced CVR, and negative (paradoxical) CVR. Wilcoxon 2-sample tests (2-sided, α = 0.05) were used to determine whether the 3 groups differed with respect to change in CVR following bypass surgery. RESULTS: The group with normal preoperative CVR demonstrated no significant change in CVR following bypass surgery (mean, 0.22% ± 0.05% to 0.22% ± 0.01%; P = .881). The group with reduced preoperative CVR demonstrated a significant improvement following bypass surgery (mean, 0.08% ± 0.05% to 0.21 ± 0.08%; P < .001), and the group with paradoxical preoperative CVR demonstrated the greatest improvement (mean change, −0.04% ± 0.03% to 0.27% ± 0.03%; P = .028). CONCLUSIONS: Preoperative measurement of CVR by using CO2 BOLD MR imaging predicts the hemodynamic effect of ECIC bypass in patients with intracranial steno-occlusive disease. The technique is potentially useful for selecting patients for surgical revascularization. ACAanterior cerebral arteryAFNIAnalysis of Functional NeuroImagesBOLDblood oxygen level−dependentCBFcerebral blood flowCO2carbon dioxideCTACT angiographyCVRcerebrovascular reactivityDSAdigital subtraction angiographyECIC bypassextracranial-intracranial bypassFiCO2inspiratory partial pressure of CO2FLAIRfluid-attenuated inversion recoveryLleftMCAmiddle cerebral arteryMRAMR angiographyOEFoxygen extraction fractionPaCO2arterial partial pressure of carbon dioxidePETpositron-emission tomographyPetCO2end-tidal partial pressure of carbon dioxidePetO2end-tidal partial pressure of oxygenRrightSTAsuperficial temporal arteryTCDtranscranial DopplerTIAtransient ischemic attack